Mycoplasma pneumonia Infection Is Associated With an Increased Risk of Systemic Lupus Erythematosus: A Nationwide, Retrospective Cohort Study - Chu, Kuo-An; Ou, Ting-Yun; Hung, Wei-Hsin; Sung, Jie; Chen, Weishan; Lin, Cheng-Li; Hung, Yao-Min; Wei, James Cheng-Chung (Frontiers in Microbiology, 2022)
Background Infections may play a role in the development of systemic lupus erythematosus (SLE). Objective To assess the link between Mycoplasma pneumonia (M. pneumonia) infection and the incidence of SLE. Method We conducted a retrospective cohort study, which identified 116,043 hospitalized patients with M. pneumoniae between 2000 and 2012 from the Taiwan National Health Insurance Research Database and compared them with 447,839 matched inpatients who had never been diagnosed with M. pneumonia infection (at a 1:4 ratio, matched by age, gender, and index year). Their comparative risk of developing SLE was evaluated. The follow-up period was defined as the time from the initial diagnosis of M. pneumonia infection to the date of SLE diagnosis, or December 31, 2013. The incidence rates of SLE were assessed in people with and without M. pneumoniae infection. Cox proportional hazard models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs), with the uninfected group used as the reference. Results The adjusted HR of SLE for the M. pneumoniae group was 2.97 with 95% CI = 2.18–4.05 compared with the uninfected group. The risk was most significantly higher within 0.5 years after the M. pneumoniae infection with an adjusted HR of 6.18 (95% CI = 3.82–9.97, p < 0.01). The adjusted HR for SLE from 0.5 to 2 years and from 2 to 5 years after M. pneumoniae infection was 1.59 (95% CI = 0.70–3.59, p = 0.27) and 2.42 (95% CI = 1.22–4.81, p = 0.01), respectively. Conclusion The incidence of SLE was significantly higher in subjects infected with M. pneumoniae.